The role of health beliefs and health literacy in women's health promoting behaviours based on the health belief model: a descriptive study - Mahla Ghorbani-Dehbalaei; Marzeyeh Loripoor; Mostafa Nasirzadeh (BMC, 2021)
Abstract Background Health literacy and health beliefs are factors that can effectively contribute to adoption of preventive behaviors among women. The present study was done to explore the role of health beliefs and health literacy in women's health promoting behaviors based on the health belief model (HBM). Methods The descriptive study was conducted in 2020 on 431 female students of Rafsanjan University of Medical Sciences (RUMS) who had been selected through stratified sampling. Data collection tool was a questionnaire which covered eight demographic information, 41 health literacy questions and 50 researcher-developed questions of health belief based on HBM constructs. Data were collected electronically and SPSS version 20 and independent t-test, one-way ANOVA, Pearson correlation coefficient and Multiple Linear Regression were used for data analysis at a significance level less than 0.05. Results The preventive behaviors were adopted by 75.57% of the population and the total health literacy score was found to be 52.71 out of 100. According to the Multiple regression analysis, self-efficacy (β = 0.414, p = 0.001) and cues to action (β = 0.299, p = 0.001) were found to be the first and second robust predictors of behavior, respectively. Health literacy, self-efficacy, cues to action and perceived susceptibility constructs predicted 52.1% of preventive behaviors. Conclusion It is recommended that researchers design, implement and evaluate interventions based on behavioral change theories, especially the self-efficacy theory, in order to promote women's health.